THE POTENTIAL OF VIRGIN COCONUT OIL (VCO) CAN INHIBIT THE DEVELOPMENT OF TUBERCULOSIS BACTERIA - Suryani, Suryani; Lestari, Rinda; Rosita, Betti; Marisa, Marisa; Slamet, Nangsih Sulastri; Mardhatillah (JURNAL KATALISATOR, 2024)
Virgin Coconut Oil (VCO) contains biochemical components, namely peptides called bacteriocins and can inhibit the growth of pathogenic bacteria. Tuberculosis (TB) is a disease caused by the pathogenic bacterium Mycobacterium tuberculosis. It has been widely studied that the potential of VCO to inhibit the growth of pathogenic bacteria such as inhibiting the growth of bacteria that cause Otitis Media Suppurative Khronis, such as Staphilocoous aureus, Staphilococcus edpidermidis, Klebsiella, Proteus, Pseudomanas aureginosa and others. But not many have studied the potential of Virgin Coconut oil to inhibit the growth of pathogenic bacteria that cause tuberculosis. Tuberculosis is very dangerous, because it attacks the lungs and other parts of the body, and is the leading cause of death worldwide. If VCO has the potential to inhibit the growth of pathogenic bacteria that cause tuberculosis, then the risk of death can be reduced. The purpose of this study is to study the potential of virgin coconut oil (VCO) to inhibit the development of tuberculosis bacteria. This research was conducted at the Chemistry Laboratory and Molecular Biology Laboratory of Perintis University Indonesia. The sample was the sputum of 5 TB patients from Pariaman Hospital, to be isolated for pathogenic bacteria. VCO is made by fermentation without the addition of a stater. It turns out that the bacteria isolated from sputum are Mycobacterium tuberculosis. VCO has the ability to inhibit the bacteria that cause tuberculosis, according to its concentration, the largest is at a concentration of 100%. Its antioxidant ability is among the weak ones. In general, VCO can be concluded that VCO has the potential to reduce the consequences of death.